Circulating ensembles of tumor‐associated cells: A redoubtable new systemic hallmark of cancer. Issue 12 (16th December 2019) - Akolkar, Dadasaheb; Patil, Darshana; Crook, Timothy; Limaye, Sewanti; Page, Raymond; Datta, Vineet; Patil, Revati; Sims, Cynthe; Ranade, Anantbhushan; Fulmali, Pradeep; Fulmali, Pooja; Srivastava, Navin; et al.
Abstract : Circulating ensembles of tumor‐associated cells (C‐ETACs) which comprise tumor emboli, immune cells and fibroblasts pose well‐recognized risks of thrombosis and aggressive metastasis. However, the detection, prevalence and characterization of C‐ETACs have been impaired due to methodological difficulties. Our findings show extensive pan‐cancer prevalence of C‐ETACs on a hitherto unreported scale in cancer patients and virtual undetectability in asymptomatic individuals. Peripheral blood mononuclear cells (PBMCs) were isolated from blood samples of 16, 134 subjects including 5, 509 patients with epithelial malignancies in various organs and 10, 625 asymptomatic individuals with age related higher cancer risk. PBMCs were treated with stabilizing reagents to protect and harvest apoptosis‐resistant C‐ETACs, which are defined as cell clusters comprising at least three EpCAM + and CK + cells irrespective of leucocyte common antigen (CD45) status. All asymptomatic individuals underwent screening investigations for malignancy including PAP smear, mammography, low‐dose computed tomography, evaluation of cancer antigen 125, cancer antigen 19‐9, alpha fetoprotein, carcinoembryonic antigen, prostate specific antigen (PSA) levels and clinical examination to identify healthy individuals with no indication of cancer. C‐ETACs were detected in 4, 944 (89.8%, 95% CI: 89.0–90.7%) out of 5, 509 cases of cancer. C‐ETACs were detected in 255 (3%, 95% CI: 2.7–3.4%) of the 8, 493 individuals with no abnormal findings in screening. C‐ETACs were detected in 137 (6.4%, 95% CI: 5.4–7.4%) of the 2, 132 asymptomatic individuals with abnormal results in one or more screening tests. Our study shows that heterotypic C‐ETACs are ubiquitous in epithelial cancers irrespective of radiological, metastatic or therapy status. C‐ETACs thus qualify to be a systemic hallmark of cancer. Abstract : What's new? Circulating Ensembles of Tumor Associated Cells (C‐ETACs) comprised of tumor emboli, immune cells, and fibroblasts pose well‐recognized risks of thrombosis and aggressive metastasis. However, the detection and characterization of C‐ETACs have been impaired by methodological difficulties. Here, the authors have developed a label‐free non‐mechanical process that permits enrichment of viable apoptosis‐resistant C‐ETACs from peripheral blood. They show that heterotypic C‐ETACs are not merely incidental findings in cancer but rather a systemic manifestation of malignancy. C‐ETACs are present in a significant proportion of all solid organ malignancies and are rare in asymptomatic individuals. Monitoring of C‐ETACs could help inform cancer management.